On the Performance of Adaptive MIMO-OFDM Indoor Visible Light Communications - Hong, Yang; Wu, Tesi; Chen, Lian-Kuan (IEEE photonics technology letters, 2016)
In this letter, we propose an adaptive indoor multiple input and multiple output (MIMO) orthogonal frequency division multiplexing (OFDM) visible light communication (VLC) system using a receiver module with angular diversity. In order to improve the capacity of indoor MIMO-OFDM VLC systems, tilted receivers are utilized to increase channel diversity, thus reducing channel correlation. With the help of singular value decomposition-based technique, which decomposes the MIMO VLC channels into independent parallel sub-channels, adaptive resource allocation, namely, bit and power loading, is used for these sub-channels to further improve the proposed system's capacity. Based on a 4 × 4 indoor MIMO-OFDM VLC system, we investigate bit error rate (BER) performance of the proposed adaptive system with different polar angles in two typical indoor scenarios. Numerical simulation results show that with 50-MHz modulation bandwidth, average BER can be improved from 4.97 × 10 -3 to 1.66 × 10 -5 and from 1.90 × 10 -3 to 1.59 × 10 -6 for the two scenarios, respectively.